The effect of dexpanthenol on the formation of epidural fibrosis in an experimental laminectomy model in rats - Kızılay, Zahir; Kahraman Çetin, Nesibe; Yaycıoğlu, Soner; Yay, Murat Özcan; Öztürk, Hakan; Yenisey, Çiğdem (Journal of Surgery and Medicine, 2020)
Aim: Epidural fibrosis, which develops after spinal surgery, is one of the factors which reduce the chances of successful surgery in the medium and long term by tightly surrounding the dura and spinal roots. In this experimental study, the aim was to compare the effects of local and systemic administration of dexpanthenol on epidural fibrosis formation in rats. Methods: Twenty-eight rats were randomly divided into 4 equal groups (control, Spongostan, local dexpanthenol and systemic dexpanthenol) and laminectomy was performed at the T11 level. Local dexpanthenol (500mg/kg) was administered with Spongostan, and systemic dexpanthenol (500 mg/kg) was administered once a day for three weeks. Epidural fibrosis, arachnoidal involvement, fibroblast cell count, vascular endothelial growth factor, and hydroxyproline levels were evaluated. Results: The grade of epidural fibrosis, fibroblast cell counts, and hydroxyproline levels were significantly lower in the systemic dexpanthenol groups (P=0.025). Conclusion: Dexpanthenol may be used as potential agent for reducing epidural fibrosis. However, it should be administered more than once for it to take effect.